2000
DOI: 10.1021/jp991953q
|View full text |Cite
|
Sign up to set email alerts
|

Vapor−Liquid Equilibrium and Critical Line of the CO2 + Xe System. Critical Behavior of CO2 + Xe versus CO2 + n-Alkanes

Abstract: An acoustic technique was applied to investigate the binary critical behavior of the system CO2 + Xe. The critical line of this binary system exhibits a temperature minimum, suggesting the existence of azeotropic behavior. The compositions of the studied mixtures were chosen in order to define the minimum temperature locus (p = 6.04 MPa, T = 282.34 K and at x(CO2) = 0.3622). The results were correlated with the Peng−Robinson equation of state using conventional mixing and combining rules. Additionally, the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…The principle of the acoustic technique and the accuracy of the method when applied to multicomponent mixtures is described elsewhere. 23 Apart from the systems that exhibit an azeotropic behaviour, the minimum in the speed of sound obtained experimentally does not correspond to the real critical point of a mixture where the compressibility remains Ðnite. The mixture becomes mechanically unstable before reaching the compressibility divergence that occurs at the pseudocritical point.24 However, the acoustic method can be proposed as an accurate experimental technique to determine critical data of multicomponent mixtures whenever the separation between the critical and pseudo-critical curves is of the same order of magnitude as the experimental error.…”
Section: Introductionmentioning
confidence: 83%
“…The principle of the acoustic technique and the accuracy of the method when applied to multicomponent mixtures is described elsewhere. 23 Apart from the systems that exhibit an azeotropic behaviour, the minimum in the speed of sound obtained experimentally does not correspond to the real critical point of a mixture where the compressibility remains Ðnite. The mixture becomes mechanically unstable before reaching the compressibility divergence that occurs at the pseudocritical point.24 However, the acoustic method can be proposed as an accurate experimental technique to determine critical data of multicomponent mixtures whenever the separation between the critical and pseudo-critical curves is of the same order of magnitude as the experimental error.…”
Section: Introductionmentioning
confidence: 83%
“…Our acoustic method 9 was applied to measure critical data of this binary system. A detailed description of the apparatus and experimental procedure can be found in our earlier publication on CO 2 + Xe mixtures …”
Section: Application Of the Acoustic Methods To The Binary System Met...mentioning
confidence: 99%
“…Indeed, the impression is often given that there is no clear relationship between critical states of mixtures and experimentally observed slowing of the speed of sound. On the other hand, since strong divergences in the thermodynamic properties of critical mixtures are generally not observable, an acoustic method using the ultrasound time-delay technique has been developed for detecting critical points in binary and ternary 8 fluid mixtures. Like any other new method, it needs some sort of validation, preferably both experimental and theoretical explanations.…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that acoustic techniques can be used to locate the critical points of quite a wide range of mixtures [19][20][21][22][23][24], and that, when comparisons have been made, the critical points measured acoustically are within experimental error of those measured by conventional optical techniques [25]. However, acoustic propagation methods are cumbersome when used in coexistence regions due to the presence of multiple velocities, with the likelihood of overlapping waveforms.…”
Section: Introductionmentioning
confidence: 94%